Shadow country [compact disc, unabridged] : a new rendering of the Watson legend - Matthiessen, Peter (Blackstone Audio, 2009)
Inspired by a near-mythic event of the wild Florida frontier at the turn of the twentieth century, Shadow Country reimagines the legend of the inspired Everglades sugar planter and notorious outlaw E. J. Watson, who drives himself relentlessly toward his own violent end at the hands of neighbors who mostly admired him, in a killing that obsessed his favorite son.--From publisher description.